SOME REFLECTIONS ON ‘THE FUTURE WE WANT’: IS THE’SUSTAINABLE DEVELOPMENT’ PARADIGM AS A GUARANTOR OF ECOLOGICAL SECURITY UNDER SERIOUS THREAT? - Rangreji, Luther (UI Scholars Hub, 2013)
The Rio+20 Declaration on the “Future We Want”, is a political document that conveys the aspirations of the international community and provides a blueprint for a programmatic action to ensure sustainable development for the future. The six sections which the “Future we Want” focusses are: a shared common vision; renewing political commitment; green economy; institutional framework for strengthening sustainable development; framework for action; and means of implementation. For reasons of felicity the paper is divided into the following sections: (i) the general conceptual framework of sustainable development; (ii) Right to Development and eradication of poverty; (iii) Role of Green economy in guaranteeing sustainable development; (iv) Financial resources and transfer of technology; (v) Roadmap for the Future of sustainable development. The paper will endeavour to investigate the ‘sustainability of sustainable development paradigm’ based on two critical themes, namely: (a) whether the paradigm of ‘sustainable development’ that guarantees ecological security is under a serious threat, as was evident from the attitudes of developed countries at the Rio+20 Conference; and (b) possible solutions, based on the principles of common but differentiated responsibilities (CBDR) and equity which are imperative to sustain and further strengthen the existing international legal order by consolidation of principles of ‘solidarity’ and international cooperation among all countries, to be able to achieve sustainable development for preservation of planet Earth and future generations.